2013
DOI: 10.1007/s00540-013-1718-1
|View full text |Cite
|
Sign up to set email alerts
|

Implications of dedicated tracheostomy care nurse program on outcomes

Abstract: The support of a specialist tracheostomy nurse can decrease complication rates and readmissions to the ICU and reduce ALOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 13 publications
1
35
0
2
Order By: Relevance
“…This study mirrors a trend within health care toward specialized and/or multidisciplinary tracheostomy care. [15][16][17][18][19] Sodhi et al 15 found that a specialized tracheostomy service resulted in nearly 30% fewer complications, fewer readmissions to the ICU secondary to tracheostomy-related complications, and decreased aver-age length of hospital stay. Norwood et al 16 found that a respiratory therapist-led team that followed patients with tracheostomy tubes from the ICU to discharge resulted in a significant decrease in tracheostomyrelated complications.…”
Section: Discussionmentioning
confidence: 99%
“…This study mirrors a trend within health care toward specialized and/or multidisciplinary tracheostomy care. [15][16][17][18][19] Sodhi et al 15 found that a specialized tracheostomy service resulted in nearly 30% fewer complications, fewer readmissions to the ICU secondary to tracheostomy-related complications, and decreased aver-age length of hospital stay. Norwood et al 16 found that a respiratory therapist-led team that followed patients with tracheostomy tubes from the ICU to discharge resulted in a significant decrease in tracheostomyrelated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Mediante la creación de unidades intermedias o de grupos multidisciplinarios, se puede mejorar el resultado de este seguimiento [6,7,9,[12][13][14][37][38][39][40]. El cuidado multidisciplinar es una intervención compleja y de difícil valoración debido a sus múltiples componentes, siendo discutible definir quién debe constituir este equipo [7].…”
Section: Discussionunclassified
“…Aunque el objetivo fundamental de este proyecto y de la constitución de un equipo multidisciplinar es intentar mejorar la calidad y seguridad del paciente con cánula, para disminuir el número de incidentes y muertes, es posible que se deriven otros beneficios. Varios autores afirman que desciende el número de readmisiones en UCI [12,16,39] y al seguir unos estrictos protocolos, se calcula que el periodo de decanulación se reduce hasta en un 20% [12,13], lo que trae como consecuencia un acortamiento de la estancia hospitalaria [9,[12][13][14], suponiendo un gran ahorro para el sistema sanitario, dado el gasto que generan estos pacientes. Por otra parte, y para finalizar, el riesgo que entraña este procedimiento provoca litigios, en los que el ORL y los profesionales de enfermería son los más frecuentemente demandados, fundamentalmente por negligencia en los cuidados postoperatorios (81%), lo que ratifica la importancia de un entrenamiento apropiado, de un registro de las actuaciones y de la existencia de un equipo multidisciplinar organizado [48].…”
Section: Discussionunclassified
“…Several studies have shown that implementation of these teams leads to decreased ICU readmissions, complications, greater decannulation rates, and decreased length of stay. [9][10][11][12] The efficacy of these tracheostomy teams in improving patient outcomes is clear, and likely also would improve outpatient outcomes and hospital readmissions by implementing standardized follow-up and decannulation protocols.…”
Section: Inpatient Complicationsmentioning
confidence: 99%